Experiências de uma professora com livros didáticos: a emergência de uma educadora - Denise de Souza Silva Pinto (2020)
This autobiographical narrative survey (BARKHUIZEN et al, 2014; BELL, 2002; CLANDININ & CONNELLY, 2000; MELLO, 2010) sought to understand the role of textbooks/materials, especially Alive!, in the professional career of the teacher / researcher teaching English in the public school. Data generation took place through a retrospective narrative covering her pedagogical experiences since the beginning of his career in the 90s, focusing on the mediation of books/teaching materials, as well as reflective diaries exploring the experiences of 2016 afforded by Alive! from viewing the video recording of the classes. The methodology of phenomenological/experiential analysis (CRESWELL et al, 2007; MICCOLI, 1997-2019) and complex (BORGES; PAIVA, 2011; HIVER, 2015; LARSEN FREEMAN, 1997, 2015; LARSEN FREEMAN; CAMERON, 2008; PAIVA , 2005, 2009; VESPOOR, 2015) allowed the documentation of (1) distinct experiences for each book / material used by the teacher / researcher, (2) two attractor states that characterize these experiences and (3) a transitional experience that disturbs the attractor state experienced for decades. The experiences accommodated in the motivational attractor state resulted from the teacher / researcher's relationship with formal and structural textbooks/materials, characterizing her as an active teacher, distant from her personal identity shaped by social activism, The emergence of a bifurcation to the attractor state was identified through an interdisciplinary, intercultural and critical teaching experience in literature classes, having opened a possibility of teaching for life. It was evidenced a change in the pedagogical system of the teacher/researcher to an educator attractor state when finding, in the book Alive!, an emancipatory proposal for the teaching of English that, combined with her ideals of education for life and social justice (BARKER, 2018; BLAKE, 2015; BONDY et al, 2017; BOYLAN; WOOLSEY, 2015), modifies her emotion for self-worth, sustaining cycles of transformations of her conceptual, projective, social experiences to teach critically and interculturally. The results pointed to five dimensions of the alliance established by the teacher/researcher with Alive! at the emotional, operational, formative, reflective and synergistic level. The research confirmed the complexity of the pedagogical experiential system modulated by the textbooks/materials, pointing the personal and emotional domain as preponderant for its evolution, as well as the importance of shared experiences with other teachers in the school context. The data corroborate the centrality of textbooks (LIMA, 2012; PAIVA, 2014; SIQUEIRA, 2012; TÍLIO, 2008) as elements that influence the teaching trajectory, unveiling the strength of a material with wide potentialities, such as the book Alive!